Forecasting Future Procurement Potential of Swedish Forest Biomass Using Forest Inventory Data - Kons, Kalvis; Athanassiadis, Dimitris; Agar, David (2023)
In the last 20 years the use of forest biomass for energy production and sawlog and pulpwood production has increased by 68%, 11% and 31% in Sweden. As Sweden is trying to achieve net zero greenhouse gas emissions by 2045, the high demand for biomass can also be expected in future. Therefore, a method to project the amount of spatially available biomass assortments for industries was developed. Available amounts of different forest assortments were estimated and visualised in a web-based tool using forest inventory data and nationwide projection analyses of available biomass for 2035–2039. In this interval, the greatest amount of available biomass and roundwood will be in Northern Sweden. Results also indicate that already existing harvesting intensity is very high compared to the available biomass in the future. The industry can expect noticeably more available biomass in the coming 100 year period. With increased competition between large pulp mills and biorefineries, the supply areas can exceed 200 km to satisfy raw material demand. The long distance and high volume supply chain requirements will demand further improvement in transportation solution nationally and cross-border in the Baltic Sea Region.